2016
DOI: 10.1002/adhm.201600772
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Breast Cancer Model on a Chip to Replicate ECM‐Activation In Vitro during Tumor Progression

Abstract: In this work, a new model of breast cancer is proposed featuring both epithelial and stromal tissues arranged on a microfluidic chip. The main task of the work is the in vitro replication of the stromal activation during tumor epithelial invasion. The activation of tumor stroma and its morphological/compositional changes play a key role in tumor progression. Despite emerging evidences, to date the activation of tumor stroma in vitro has not been achieved yet. The tumor-on-chip proposed in this work is built in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 63 publications
6
94
0
1
Order By: Relevance
“…Microfluidics technology has also been employed to study ECM alterations during active collagen, hyaluronic acid and fibronectin were also observed to be overexpressed in presence of the tumor microtissues. Using second harmonic imaging, ECM remodeling was observed in coculture condition confirming the activation of NF when co-cultured with tumor micro-tissues [178]. These studies illustrate the ease and popularity of microfluidic platforms to study various aspects of cancer invasion.…”
Section: D Microengineered Models To Study Cancer Invasionsupporting
confidence: 52%
“…Microfluidics technology has also been employed to study ECM alterations during active collagen, hyaluronic acid and fibronectin were also observed to be overexpressed in presence of the tumor microtissues. Using second harmonic imaging, ECM remodeling was observed in coculture condition confirming the activation of NF when co-cultured with tumor micro-tissues [178]. These studies illustrate the ease and popularity of microfluidic platforms to study various aspects of cancer invasion.…”
Section: D Microengineered Models To Study Cancer Invasionsupporting
confidence: 52%
“…Several studies have shown the critical role of CAFs in cancer progression, although the mechanisms by which they promote disease progression have yet to be unraveled . Given that fibroblasts are one of the key cell populations in the stroma, a number of studies have examined tumor–fibroblast interactions on chip . Integration of microfabrication along with biomaterial‐assisted cell encapsulation can be used to compartmentalize different cell populations .…”
Section: Tumor‐on‐a‐chip Modelsmentioning
confidence: 99%
“…In addition, paclitaxel also effectively inhibited the progression of the ductal carcinoma spheroids, indicated by their maintained sizes compared with the significantly increased tumor volume without the drug (Figure 3d,e). In addition, a breast-cancer-microenvironment-on-a-chip model was developed by Imparato and colleagues to replicate the interactions of breast cancer cells with the stroma and ECM activation during tumor progression [46]. In another study, Varghese and co-workers encapsulated MCF7 breast cancer cell spheroids and human umbilical vein endothelial cells (HUVECs) within a gelatin methacryloyl (GelMA) hydrogel, and then drove HUVECs to migrate to the periphery of the GelMA to form endothelial barriers [47].…”
Section: Modeling Cancer Biology and Physiology In Vitromentioning
confidence: 99%